Discovering your life blueprint : Practical mysticism - Phang, Siew Sia (Penerbit Wawasan Nusa (M) Sdn Bhd, 2014)
If you have ever asked yourself what the purpose of your life is, and what life is all about; if, even while you have been enjoying the material aspects of your life, you somehow feel restless with an emptiness in your heart, all I can say is, you have started with your search for the meaning of life and the purpose of life at a higher level of consciousness. When you seek greater meaning, a higher purpose to existence, this is an indication for you to look at your Divine Consciousness and to begin your spiritual journey. This is where it all begins. This book provides some guidance for you to tap into your Divine Consciousness to enable you to have a godlike experience in the human world. However, in order to experience this you must be ready to be receptive to new ideas and new concepts that will be introduced. Let go of your ego as it will hinder you from progressing in the right spiritual path. Our ultimate spiritual path centers around meditation. There are many ways to meditate, depending on a person's level of consciousness. It could be a very basic and simple method just to calm your mind or it could be so advanced that you will have communion or union between your Divine Consciousness and the Universal Consciousness. Certain types of meditation will reveal to you that what seems to be in our physical existence is the least of what there actually is. Only after many years of practicing meditation have I come to understand there is a "higher power" which abides within us. This is the core of Mystical Trinity Meditation [MTM].